A universal strategy to prepare sulfur-containing polymer composites with desired morphologies for lithium−sulfur batteries - Zeng, Shao-Zhong; Zeng, Xierong; Tu, Wenxuan; Huang, Haitao; Yu, Liang; Yao, Yuechao; Jin, Nengzhi; Zhang, Qi; Zou, Jizhao (American Chemical Society, 2018)
Lithium–sulfur (Li–S) batteries are probably the most promising candidates for the next-generation batteries owing to their high energy density. However, Li–S batteries face severe technical problems where the dissolution of intermediate polysulfides is the biggest problem because it leads to the degradation of the cathode and the lithium anode, and finally the fast capacity decay. Compared with the composites of elemental sulfur and other matrices, sulfur-containing polymers (SCPs) have strong chemical bonds to sulfur and therefore show low dissolution of polysulfides. Unfortunately, most SCPs have very low electron conductivity and their morphologies can hardly be controlled, which undoubtedly depress the battery performances of SCPs. To overcome these two weaknesses of SCPs, a new strategy was developed for preparing SCP composites with enhanced conductivity and desired morphologies. With this strategy, macroporous SCP composites were successfully prepared from hierarchical porous carbon. The composites displayed discharge/charge capacities up to 1218/1139, 949/922, and 796/785 mA h g–1 at the current rates of 5, 10, and 15 C, respectively. Considering the universality of this strategy and the numerous morphologies of carbon materials, this strategy opens many opportunities for making carbon/SCP composites with novel morphologies.
Keywords: carbon/sulfur composites; lithium batteries; morphological control; porous carbon nanobelts; sulfur-containing polymers